Solar desalination: Cases, synthesis, and challenges. (7th April 2020) - Delgado, William R.; Beach, Timothy; Luzzadder‐Beach, Sheryl
Abstract: Desalination will become an increasingly important water resource to supply a growing world population that will face greater water scarcity in the coming decades. Desalination processes are energy‐intensive and currently rely on fossil fuels that contribute to global warming and exacerbate the planet's water woes. Solar power, as a low‐carbon energy resource, can reduce desalination's environmental footprint. However, there are many logistical considerations to take into account when planning solar desalination projects. This paper examines six of these issues, which include: (a) the spatial distribution of solar energy and saline water, (b) modeling tools to measure the financial feasibility of solar powered desalination plants, (c) community approval, (d) interconnection policies for solar desalination plants connected to the regional grid, (e) combining solar energy with other renewable energy sources, and (f) potential carbon savings from switching to solar energy. The paper will conduct its analysis through four key case studies in El Paso, Texas, Abilene, Texas, Abu Dhabi, United Arab Emirates, and Denmark, Australia. The paper concludes with a discussion on how improved solar technology will further the economic prospects of solar desalination and an analysis of brine disposal options that include siting seawater desalination operations in waters with high circulation and explaining how brine harvesting could lead to useful economic mineral products such as sodium, chlorine, potassium, and magnesium. This article is categorized under: Engineering Water > Sustainable Engineering of Water Abstract : This article will describe the logistics and challenges of solar powered desalination projects through the context of four case studies in locations depicted above that cover these key issues.